Speed as an injury risk factor in competitive alpine ski racing depends on events - Gilgien, M.; Spörri, J.; Kröll, J.; Chardonnens, J.; Boffi, G.; Jahnel, R.; Müller, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It was postulated that speed is an important factor for the increased injury rate in competitive alpine speed events of downhill (DH) and super-giant slalom (SG) compared to giant slalom (GS) skiing (Florenes et al., 2009). The speed characteristics in World Cup racing is not well described in the literature. The aims of this study were to a) map the speed distribution in men`s World Cup alpine skiing for the events of GS, SG and DH, and to b) elaborate on potential susceptibility to injuries as result of speed differences between the events. Method: Forerunners speed was captured in 6 GS, 2 SG and 4 DH men`s World Cup races with a Global Navigational Satellite System (GNSS). The differential GNSS Doppler signal was recorded at 50 Hz using the GPS/GLONASS (L1/L2) with an antenna G5Ant-2AT1 (Antcom, Torrance, CA, USA) affixed to the forerunners helmet and a receiver Alpha (Javad, San Jose, USA). The GNSS-captured speed pattern was time-normalized using the time difference between the winner and the GNSS-forerunner. The mean speed (s_mean), max speed (s_max) and the standard deviation (±SD) were computed. The relative s_mean ratio between SG and GS and between DH and GS was calculated. Based on the s_mean we calculated the mean kinetic energy (Ekin_mean) for GS, SG and DH using skier`s mass of 100kg (Neumayr et al., 2003). The Ekin_mean ratio between the race events was computed in relation to the Ekin_mean of GS. Results: For GS: s_mean = 66 km/h (±13 km/h) and s_max = 96 km/h. For SG: s_mean = 86 km/h (±16 km/h) and s_max =121 km/h. For DH: s_mean = 96 km/h (±20 km/h) and s_max =143 km/h. The s_mean ratio for SG/GS was 1.31 and for DH/GS = 1.47. Ekin_mean for GS was 17kJ (±7kJ), for SG was 28kJ (±12kJ) and for DH it was 36kJ (±17kJ). The ratio for Ekin_mean was 1.72 for SG/GS and 2.16 for DH/GS. Discussion: Fifty % increase in s_mean from GS to DH results in doubling of kinetic energy. This is significant in regard to the forces that occur in racer`s falls, since the force ratio between GS and DH are equal to the energy ratio. From our analysis, we postulate that the potential for injuries may be associated with the speed differences between the events. Future investigations may pinpoint more accurately the potential factors responsible for ski related injuries.